Encountering Anger in the Emergency Department: Identification, Evaluations and Responses of Staff Members to Anger Displays - Arik, Cheshin; Anat, Rafaeli; Arie, Eisenman (Emergency Medicine International, 2012)
Background. Anger manifestations in emergency departments (EDs) occur daily, interrupting workflow and exposing staff to risk. Objectives. How staff assess and recognize patients’ angry outbursts in EDs and elucidate responses to anger expressions, while considering effects of institution guidelines. Methods. Observations of staff patient interaction in EDs and personal interviews of staff (n=38) were conducted. Two questionnaires were administered (n=80 & n=144). Assessment was based mainly on regression statistic tests. Results. Staff recognizes two types of anger displays. Magnitude of anger expressions were correlated with staff’s fear level. Staff’s responses ranged from ignoring incidents, giving in to patients’ requests or immediately calling security. When staff felt fear and became angry they tended to call security. Staff was more likely to ignore anger when incident responsibility was assigned to patients. Discussion. Anger encounters are differentiated according to intensity level, which influences interpretations and response. Organizational policy has an effect on staff’s response. Conclusions. Staff recognizes anger at varying levels and responds accordingly. The level of danger staff feels is a catalyst in giving in or calling security. Call security is influenced by fear, and anger. Permanent guidelines can help staff in responding to anger encounters.